1989
DOI: 10.1080/07315724.1989.10720273
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss after gastroplasty: psychological sequelae in relation to clinical and metabolic observations.

Abstract: Twenty-one grossly obese patients were studied before and repeatedly after gastroplasty. Eighteen months after surgery, three groups of patients were identified which had similar preoperative weights but showed significantly different patterns of weight loss. About one third of the patients were considered unsuccessful (less than 20% weight loss). Psychological assessment, using the meta-contrast technique, showed that signs of regressive defense and of immature identity decreased postoperatively. Mild to mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Moreover, not all studies found an overall positive outcome in depression [23]. One study even reported an increase of depression after bariatric operation [24]. To further clarify the association between changes in symptoms of depression in bariatric patients, controlled, long-time studies are clearly needed.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, not all studies found an overall positive outcome in depression [23]. One study even reported an increase of depression after bariatric operation [24]. To further clarify the association between changes in symptoms of depression in bariatric patients, controlled, long-time studies are clearly needed.…”
Section: Introductionmentioning
confidence: 98%
“…Studies using projective techniques that require a high level of inference to interpret were also not reviewed. 48 Studies on intestinal bypass surgery were not reviewed, since intestinal bypass surgery is considered to be obsolete today and has been abandoned. Table 1 illustrates the inclusion and exclusion criteria of this review.…”
Section: Methodsmentioning
confidence: 99%
“…Ryden et al . suggest that the marked weight loss as such leads to problems of adaptation which in turn may trigger depressive reactions 31 . We think that this applies to case 1.…”
Section: Discussionmentioning
confidence: 81%